Serwa Boateng's guide to witchcraft and mayhem - Brown, Roseanne A. (Brown, Roseanne A. Serwa Boateng, 2023)
In order to steal the Midnight Drum and free her powerful grandmother, twelve-year-old vampire Serwa deceptively collaborates with her rival Declan, a Slayer, but joining forces compels Serwa to confront truths about herself she has tried hard to deny.